1993
DOI: 10.1002/jmri.1880030409
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of cine MR velocity measurements in the internal carotid artery with collateral flow in the circle of willis: Preliminary study

Abstract: The velocity-phase relationship intrinsic to phase-contrast magnetic resonance (MR) angiography permits the quantitative and qualitative assessment of blood flow. The ability to measure velocity and vessel cross-sectional area allows noninvasive assessment of volume flow rate (VFR) in the internal carotid artery (ICA). Phase-contrast techniques also demonstrate flow direction. Using two-dimensional cine phase-contrast angiography, the authors evaluated VFR in the ICA and collateral flow about the circle of Wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…MRA has demonstrated high sensitivity in evaluation of component vessels in the CW. [ 29 ] Though well-accepted clinically, sensitivity of 3D time-of-flight (TOF) MRA depends on the blood flow velocity of the vessel, and the technique may have difficulties in visualizing small vessels in the CW with slow or turbulent flow. [ 34 ] In most studies, MRA 3D acquisitions were made with either steady state precession (FSSP) or spoiled gradient technique (SPGR) using 1.5-tesla systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRA has demonstrated high sensitivity in evaluation of component vessels in the CW. [ 29 ] Though well-accepted clinically, sensitivity of 3D time-of-flight (TOF) MRA depends on the blood flow velocity of the vessel, and the technique may have difficulties in visualizing small vessels in the CW with slow or turbulent flow. [ 34 ] In most studies, MRA 3D acquisitions were made with either steady state precession (FSSP) or spoiled gradient technique (SPGR) using 1.5-tesla systems.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have investigated the role of the CW in the development of collateral flow in ICA obstruction; these studies were based on mathematical models[ 17 18 19 ] and used transcranial Doppler ultrasound,[ 20 21 22 23 24 25 ] digital contrast–enhanced angiography,[ 3 26 ] or magnetic resonance angiography (MRA). [ 2 3 27 28 29 ] MRA has previously been shown to be well-suited to investigate the CW, in view of the fact that it is able to provide morphological as well as hemodynamic information concerning blood flow direction in individual vessels accurately. [ 30 31 ] Previous studies have demonstrated that three-dimensional time-of-flight (3D-TOF) MRA is a sensitive, noninvasive modality suitable for detecting the anatomy of the CW in healthy volunteers and patients with carotid artery disease.…”
Section: Introductionmentioning
confidence: 99%
“…The imaging parameters of the cine PC-MRI sequences in the neck and the abdomen were chosen as a compromise between the need for spatial resolution to minimize partial volume effects and to maximize high-frequency sampling of volumetric blood flow cine PC-MRI measurements at both positions (Jiang et al 2007). The initial parameters chosen were similar to those typically employed in measurements using cine PC-MRI in the measurement of ICA (Davis et al 1993, Buijs et al 1998, Ford et al 2005, Oktar et al 2006 and those used for fast cine PC-MRI of the AA (Caruthers et al 2003, Lin et al 2004, Waters et al 2005, Grotenhuis et al 2006. These parameters were then modified by reducing spatial resolution to increase the speed of acquisition and optimized to maximize relative signal intensity differences of stationary and flowing tissue, which has been shown to help reduce the impact of partial volume effects (Jiang et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Initial cine PC-MRI parameters for measuring flow in ICA and VA were selected from the literature (Davis et al 1993, Buijs et al 1998, Ford et al 2005, Oktar et al 2006: a Turbo Field Echo (TFE) sequence with linearly filled, Cartesian k-space, TE 3.2 ms, TR 15 ms, flip angle 15 • , field of view 200 × 170 cm, slice thickness 10 mm, SENSE factor 2, velocity sensitivity (VENC) 70 cm s −1 each single cine PC-MRI yielding 20 cardiac phase measurement points reconstructed retrospectively per R-to-R cardiac interval. This multi-shot TFE sequence acquires 2 k-space lines within a segment duration of twice the repetition time, yielding an acquired temporal resolution of 60 ms.…”
Section: Selection and Validation Of Mri Sequence Imaging Parametersmentioning
confidence: 99%
“…Such flow rates are of arterial perfusion, not of brain regional perfusion. Phase-contrast MRI studies have virtually unanimously found an association between an increasing degree of carotid stenosis and a reduction in flow rates through the internal carotid artery (ICA) and, when assessed, increased collateral use [ 4 – 15 ]. However, until recently, no PC-MRI studies assessed near-occlusions separately.…”
Section: Introductionmentioning
confidence: 99%